Validitas Bahan E-Module Berbasis Android pada Operasi Count Fractional Kelas V SD - Hendrian Syahputra; Dea Mustika (IJoIS: Indonesian Journal of Islamic Studies, 2022)
The purpose of this study is the validity of the android-based E-module on the material for calculating fractions in grade 5 SDN 193 Pekanbaru. This method uses development research with the ADDIE development model. This research was conducted in three stages, namely 1) the analysis stage consisted of educator analysis, student analysis and learning material analysis; 2) the design stage consists of designing rpp, designing an android-based E-module design using the Ms. Word application and converting docx files into PDF; 3) the development stage is the process of realizing the design into a real product. The results of this study show that the android-based E-module meets the very valid criteria. In the first validation, it obtained an average result of 71.43% with a fairly valid category that was declared feasible for use with revisions. Then the researcher made some improvements that had been given by the validators so that in the second validation obtained an average result of 95.94% with a very valid category, then the android-based E-module was feasible to use for the learning process. So it can be concluded that the android-based E-module is feasible to use without revision with the category of validity reaching a very valid level by conducting validation tests twice to the validators.